2015
DOI: 10.1038/bjc.2015.432
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the best complete blood count-based predictors for bladder cancer outcomes in patients undergoing radical cystectomy

Abstract: Background:We sought to determine which parsimonious combination of complete blood count (CBC)-based biomarkers most efficiently predicts oncologic outcomes in patients undergoing radical cystectomy (RC) for bladder cancer (BC).Methods:Using our institutional RC database (1992–2012), nine CBC-based markers (including both absolute cell counts and ratios) were evaluated based on pre-treatment measurements. The outcome measures were recurrence-free survival (RFS), cancer-specific survival (CSS), and overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 29 publications
1
68
0
Order By: Relevance
“…The NLR data were collected before surgery or chemotherapy in the included studies. The cut-off values for the NLR ranged from 2 to 5, and the cut-off value was not specified in 3 studies [15, 35, 38]. In Mano’s study, there were two cut-off values, one each to evaluate the prognostic role of the NLR in progression-free survival (PFS) and relapse-free survival (RFS) [31].…”
Section: Resultsmentioning
confidence: 99%
“…The NLR data were collected before surgery or chemotherapy in the included studies. The cut-off values for the NLR ranged from 2 to 5, and the cut-off value was not specified in 3 studies [15, 35, 38]. In Mano’s study, there were two cut-off values, one each to evaluate the prognostic role of the NLR in progression-free survival (PFS) and relapse-free survival (RFS) [31].…”
Section: Resultsmentioning
confidence: 99%
“…, 2013; Kudo-Sakamoto et al. , 2014; Trillsch et al. , 2016), suggesting that the mechanism of cadherin regulation reported here may apply to other cadherins in a variety of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that E-cadherin cleavage by calpain is involved in tumor progression (Ye et al. , 2013; Trillsch et al. , 2016) and that calpain cleavage of N-cadherin reduces cell–cell adhesion (Jang et al.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of 24 recent studies investigating the prognostic role of NLR in RCC according to treatment type is shown in Tables 8–11 . Table summarizes studies investigating the prognostic role of preoperative NLR in patients who underwent transurethral resection for NMIBC.…”
Section: Differential Blood Cell Markersmentioning
confidence: 99%